Africa agriculture transformation scorecard: performance and lessons - Matchaya, Greenwell C.; Kasoma-Pele, Winnie; Samikwa, D. (AKADEMIYA2063, 2024)
The Malabo Declaration on accelerated agricultural growth and transformation for shared prosperity and improved livelihoods is a set of goals that were adopted by Heads of State and Government of the African Union in 2014 in Malabo, Equatorial Guinea (AUC 2014). To translate the seven Malabo commitments into results, a call for action was made by the Heads of State and Governments, by calling upon the AU Commission and the NEPAD Planning and Coordinating Agency, in collaboration with partners, to initiate a review process to be conducted on a biennial basis starting 2017, with an objective of tracking, measuring, and reporting progress towards achieving the Malabo Declaration commitments by 2025. Four Biennial Reviews (BR) have been conducted—the inaugural BR in 2017, the second BR in 2019, the third BR in 2021, and the most recent BR concluded in 2023. This brief outlines the performance of the SADC region and its Member States in advancing the seven Malabo Declaration commitments mentioned earlier, based on the BR4 report. This brief also details the SADC region’s challenges and lessons learned from the review processes. Additionally, it reviews policy and programmatic changes in the SADC region influenced by insights from the inaugural BR1 in 2017 (AUC 2018), BR2 in 2019 (AUC 2020), BR3 in 2021 (AUC 2022), and BR4 in 2023 (AUC 2024) in line with Matchaya et al. (2021). The brief concludes by highlighting necessary policy actions that the 16 SADC countries (Angola, Botswana, Comoros, Democratic Republic of Congo, Eswatini, Lesotho, Madagascar, Malawi, Mauritius, Mozambique, Namibia, Seychelles, South Africa, Tanzania, Zambia, and Zimbabwe) would have to take to achieve the Malabo Declaration’s targets by 2025. A key recommendation from the analysis indicates the need for developing robust M&E and data systems to improve data quality and strengthen the evidence base for agricultural-based economic transformation. This is also the time to strengthen M&E systems as post-Malabo strategies are being developed. To guarantee seamless monitoring, the SADC Member States should ensure that all key BR indicators are featured in their future NAIPs.